Comparison of the use of lung ultrasound and chest radiography in the diagnosis of rib fractures: a systematic review. Issue 3 (23rd November 2018) - Battle, Ceri; Hayward, Simon; Eggert, Sabine; Evans, Phillip Adrian
Abstract : Introduction: It is well-recognised that the detection of rib fractures is unreliable using chest radiograph. The aim of this systematic review was to investigate whether the use of lung ultrasound is superior in accuracy to chest radiography, in the diagnosis of rib fractures following blunt chest wall trauma. Methods: The search filter was used for international online electronic databases including MEDLINE, EMBASE, Cochrane and ScienceDirect, with no imposed time or language limitations. Grey literature was searched. Two review authors completed study selection, data extraction and data synthesis/analysis process. Quality assessment using the Quality Assessment of Diagnostic Accuracy Studies Tool (QUADAS-2) was completed. Results: 13 studies were included. Overall, study results demonstrated that the use of lung ultrasound in the diagnosis of rib fractures in blunt chest wall trauma patients appears superior compared with chest radiograph. All studies were small, single centre and considered to be at risk of bias on quality assessment. Meta-analysis was not possible due to high levels of heterogeneity, lack of appropriate reference standard and poor study quality. Discussion: The results demonstrate that lung ultrasound may be superior to chest radiography, but the low quality of the studies means that no definitive statement can be made.